CORRELATION BETWEEN MORTALITY RATE AND ORGAN DYSFUNCTION DUE TO SEVERE SEPSIS - PETTERLE, Ricardo Rasmussen; YOUSSEF, Nazah Cherif Mohamad; MAZEPA, Melissa Mello; OLIVEIRA, Renan Sandrei de (Brazilian Journal of Biometrics, 2016)
Severe sepsis and multiorgan syndrome dysfunction are among the leading causes of mortality in Intensive Care Units (ICUs) as well as being responsible for long periods of hospitalization and high treatment costs. This article aimed to model the mortality due to severe sepsis and multiorgan syndrome dysfunction from a set of covariates using binary logistic regression. The data of 159 patients admitted in the ICU (HC-UFPR) were analyzed in the period january to december 2013. The results showed that the presence of renal and/or central nervous system dysfunction/failure in the first 24 hours of hospitalization in ICU is associated with higher mortality rate. We verified that a patient with renal dysfunction/failure who was diagnosed with SOFA score 4 has five times more chance to evolve to death when compared to a patient with a SOFA score 0. Regarding the central nervous system dysfunction/failure a patient with SOFA score 4 has three times more likely to evolve to an adverse outcome when compared with other patient who has a SOFA score of 0 in admission in ICU.